2021
DOI: 10.2147/idr.s319029
|View full text |Cite
|
Sign up to set email alerts
|

Delayed SARS-CoV-2 Clearance in Patients with Obesity

Abstract: Objective The present study aimed to investigate the correlation between obesity and virus persistence in patients with COVID-19. Design and Methods A total of 57 patients with laboratory-confirmed COVID-19 were admitted to two clinical centers, and data were analyzed retrospectively. Among them, 18 patients with body mass index (BMI) ≥ 25 kg/m 2 were diagnosed with obesity, and dynamics of viral replication were compared. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Even after correcting for several other factors, the Black, Asian, and Minority Ethnic (BAME) groups are at very high risk of death from COVID-19 infection, according to current mortality [70]. COVID-19 infection is more likely in those with metabolic risk factors such as obesity, diabetes, and cardiovascular disease, according to numerous research [71][72][73]. In addition, Plasma proteome examination recognized COVID-19 disease biomarkers progression, and the important pathways are platelet degranulation, complement system, and coagulation cascades.…”
Section: Markers For Covid-19 In Pco Patientsmentioning
confidence: 99%
“…Even after correcting for several other factors, the Black, Asian, and Minority Ethnic (BAME) groups are at very high risk of death from COVID-19 infection, according to current mortality [70]. COVID-19 infection is more likely in those with metabolic risk factors such as obesity, diabetes, and cardiovascular disease, according to numerous research [71][72][73]. In addition, Plasma proteome examination recognized COVID-19 disease biomarkers progression, and the important pathways are platelet degranulation, complement system, and coagulation cascades.…”
Section: Markers For Covid-19 In Pco Patientsmentioning
confidence: 99%
“…[1] Many studies have summarized the characteristics of patients with COVID-19 and identified several factors associated with the viral shedding time (VST). [2][3][4][5][6][7] However, few studies have developed predictive models for the VST of the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) Delta variant.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that male, elderly, overweight COVID-19 patients have prolonged DVS [4,5]. Abnormal inflammatory indicators, such as interleukin-6 (IL-6) levels, C-reactive protein (CRP) levels, lactate dehydrogenase (LDH) levels, neutrophil count (NC), lymphocyte count (LC), and monocyte count (MC), are important factors for an extended DVS in COVID-19 patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Data are presented as the median (IQR) or n (%). P values were calculated using Wilcoxon's rank-sum test, the χ 2 test, or Fisher's exact test 4. Ensi Luo et al…”
mentioning
confidence: 99%